Monte Carlo methods for signal processing a review in the statistical signal processing context. - Doucet, A. (IEEE Signal processing magazine)
In this article, MCMC (Markov chain Monte Carlo methods) and SMC (sequential Monte Carlo methods) are introduced to sample and/or maximize high-dimensional probability distributions. These methods enable to perform likelihood or Bayesian inference for complex non-Gaussian signal processing problems.